THE BUSINESS ENVIRONMENT OF THERUSSIAN-BELARUSIAN BORDER IN THE CONTEXT OF INTERSTATE INTEGRATION - Kuzavko, Anton (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2020)
The problem considered in the article is expressed in contradiction. On the one hand, the border position of the regions provides additional opportunities for the implementation of business ideas of international trade and cooperation. On the other hand, it can significantly change the business environment in comparison with other regions of the state, increasing competition and creating additional risks for entrepreneurs. The analysis explains the reason for the lag in the level of economic development of these regions from the national one. The aim of the study is to find evidence of hypothesis that the inter-metropolitan and at the same time border position of the regions of the two states engaged in political and economic integration negatively affects the economic development and business climate of these territories, stimulates the outflow of capital and labor resources - key factors of production. To achieve the goal, various methods are used, such as in-depth interviewing, questions from entrepreneurs, a retrospective analysis of historical facts of interstate interaction, but this article describes the results of the study obtained in the course of statistical analysis. This article discusses the elements of the business environment that directly or indirectly affect the behavior of economic and their desire to build and develop business in the border areas of Russia and Belarus. It is shown that over the years of integration, the economic growth rates of the Russian-Belarusian border regions lagged behind the national ones. Wages remained lower than the national average. This provokes the outflow of intellectual capital - the most important element of the business environment. Thus, the article shows that the integration of Russia and Belarus, despite the overall positive effect for the two states, limits the rate of economic growth in the border zone.